5
$\begingroup$

Suppose $a$ is a root of $x^2 + 3x - 1.$ Find $\frac{2a^5 - 5a^4 + 2a^3 - 8a^2}{a^2 + 1}.$


I was thinking of factoring the fraction a bit first, than letting $a^2 = 1 - 3a.$ However, that leads nowhere.

$\endgroup$
11
  • 2
    $\begingroup$ Well I'd substratc $2a^5 + 6a^4 - 2a^3 = 0$ from the top and then keep subtracting multiples of $a^2 +3a -1 = 0$ and we what sort of thing I get in the end. $\endgroup$
    – fleablood
    Sep 16 '20 at 3:09
  • 1
    $\begingroup$ $(2x^3-11x^2+37x-130)(x^2+3x-1)+427x-130$ is the factorization. What next? @fleablood $\endgroup$ Sep 16 '20 at 3:22
  • $\begingroup$ I suggest something else. $\endgroup$
    – Spectre
    Sep 16 '20 at 3:23
  • $\begingroup$ Take $a^4$ out of $2a^5 - 5a^4$. $\endgroup$
    – Spectre
    Sep 16 '20 at 3:24
  • $\begingroup$ You have a linear factor there. Find that. $\endgroup$
    – Spectre
    Sep 16 '20 at 3:24
8
$\begingroup$

A complete solution. Let $a$ be a root of $x^2+3x-1$. Then

$a^2=1-3a$

$a^3=a-3a^2=a-3(1-3a)=10a-3$

$a^4=10a^2-3a=10(1-3a)-3a=10-33a$

$a^5=10a-33a^2=10a-33(1-3a)=-33+109a$

Therefore the numerator:$$2a^5 - 5a^4 + 2a^3 - 8a^2= -66+218a-5(10-33a)+2(10a-3)-8(1-3a)=-130+427a$$

and the denominator: $a^2+1=2-3a$.

Let $a'$ be another root of $x^2+3x-1=0$. Then $aa'=-1. a+a'=-3$. Multiply the numerator and the denominator by $2-3a'$. The denominator becomes $$(2-3a)(2-3a')=4+9-6(-3)=13-18=-5.$$ The numerator becomes $$(427a-130)(2-3a')= 854a-260+1281+390a'=1021-1170+464a=464a-149.$$ So the fraction is equal to $$\frac{464a-149}{-5}$$ where $$a=\frac{-3\pm \sqrt{13}}{2}.$$

$\endgroup$
9
  • $\begingroup$ I guess I was a fool.... $\endgroup$
    – Spectre
    Sep 16 '20 at 3:33
  • $\begingroup$ Fool for taking the longest route $\endgroup$
    – Spectre
    Sep 16 '20 at 3:34
  • $\begingroup$ I hoped to get an integer that way without using the actual value of $a$. But now I do not see how can one avoid substituting $a=\frac{-3\pm \sqrt{13}}{2}$. The answer is probably irrational. $\endgroup$
    – markvs
    Sep 16 '20 at 3:36
  • 1
    $\begingroup$ I fixed the calculation. But the fraction still is not completely simplified. $\endgroup$
    – markvs
    Sep 16 '20 at 3:49
  • 1
    $\begingroup$ I think the OP may have copied the fraction incorrectly. I have solved several such problems in the past. The result always did not depend on $a$. $\endgroup$
    – markvs
    Sep 16 '20 at 4:19
3
$\begingroup$

Another way.

For $a^2+3a-1=0$ and $a=\frac{-3+\sqrt{13}}{2}$ we obtain: $$(a^2-1)^2=9a^2$$ or $$(a^2+1)^2=13a^2$$ or $$a^2+1=\sqrt{13}a,$$ which gives: $$\frac{2a^5-5a^4+2a^3-8a^2}{a^2+1}=$$ $$=\tfrac{2a^5+6a^4-2a^3-11a^4-33a^3+11a^2+37a^3+111a^2-37a-130a^2+37a}{\sqrt{13}a}=$$ $$=\tfrac{37-130a}{\sqrt{13}}=\tfrac{37-65(-3+\sqrt{13})}{\sqrt{13}}=\tfrac{232-65\sqrt{13}}{\sqrt{13}}.$$ For $a=\frac{-3-\sqrt{13}}{2}$ we obtain: $$a^2+1=-\sqrt{13}a,$$ which gives $$\frac{2a^5-5a^4+2a^3-8a^2}{a^2+1}=\tfrac{-232-65\sqrt{13}}{\sqrt{13}}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.